A Two-Location Inventory Model with Transshipment and Local Decision Making - Rudi, Nils; Kapur, Sandeep; Pyke, David F. (Management Science, 2001)
In situations where a seller has surplus stock and another seller is stocked out, it may be desirable to transfer surplus stock from the former to the latter. We examine how the possibility of such transshipments between two independent locations affects the optimal inventory orders at each location. If each location aims to maximize its own profits—we call this local decision making—their inventory choices will not, in general, maximize joint profits. We find transshipment prices which induce the locations to choose inventory levels consistent with joint-profit maximization.